Three days of static stretching within a warm-up does not affect repeated-sprint ability in youth soccer players - Wong, P. -L.; Lau, P. W. C.; Mao, D. W.; Wu, Y. Y.; Behm, D. G.; Wisloff, U. (The Journal of Strength and Conditioning Research, 2011)
This study aimed to examine the repeated-sprint ability (RSA) in soccer players after 3 days of static stretching. Twenty soccer players (age: 16.8 ± 0.4 years) participated in 2 series of experiments with within-subject repeated-measure design (control series [CON]: 13-minute aerobic warm-up; and static-stretching series [SS]: 10-minute aerobic warm-up and 3-minute static stretching). Each series consisted of 5 days, and RSA (9 × 30 m separated by 25-second passive recovery) was tested on days 1 and 5. Static stretching was performed for 3 consecutive days from days 2-4, before and after intermittent aerobic endurance exercise on each day. The same warm-up protocol was used before and after all RSA tests and exercises within 1 series. No significant difference between CON and SS was observed (p > 0.05) in RSA for overall (all sprints), early phase (first to third sprints), middle phase (fourth to sixth sprints), and final phase (seventh to ninth sprints). Short-term static stretching had trivial effects (Cohen's d < 0.35) on overall and split RSA phases (early, middle, and final). The present study showed that performing static stretching for 3 consecutive days and before repeated-sprint test did not negatively affect RSA. However, it is premature to recommend that static stretching could be included in in-season daily warm-up routine because some movements such as jump and single sprint were more sensitive to static stretching.